Istikhdām an-Naẓariyyah al-Mujażżarah li Strauss fī al-Buḥūṡwa ad-Dirāsāt al-‘Arabiyyah - Himatul Istiqomah (IAIN Salatiga, 2020)
There are several theories in qualitative research including Grounded Theory (GT). It is a theory discovered, developed, and achieved by collecting and analyzing data systematically about specific phenomena. it is the result of a study called grounded Research (GR). The purpose of this study is to present the role of Strauss's Grounded research in Arabic research (PBA) and the types of GT produced. This study uses qualitative-descriptive research, with primary data sources from PBA that have been published in the last five years, namely 15 topics. The results of this study indicate that the roles of GR in PBA as a type of qualitative research are 5 topics, as a qualitative approach are 8 topics, as a qualitative method is 1 topic, and as a qualitative technique is 1 topic. In general, the role of GR is as an approach in qualitative research. The types of GT are 10 topics in the form of theory, 2 topics in the form of hypothesis, and 3 topics are in the form of assumptions. In general, the result of GR is GT in the form of theory.